Managers' psychological challenges in implementing corporate responsibility in supply chains. Issue 3 (26th February 2018) - Eriksson, David; Svensson, Göran
Abstract : Purpose: This paper aims to conceptualize managers' psychological challenges with respect to implementing corporate responsibility throughout supply chains. Design/methodology/approach: Four areas of psychological theory are introduced to expand the understanding of the challenges involved in implementing corporate responsibility in supply chains, namely, relationship and humanization theory; the number-of-people-suffering theory; superficial-identification theory; and the bystander effect theory. Findings: The common denominator between the introduced areas of psychological theory is that all consider the expected degree of corporate responsibility in supply chains to extend beyond managers' ability to cope so that failure is probable. Research limitations/implications: Supply chain management research needs to consider various psychological challenges to effectively address corporate responsibility in supply chains. This research shows that it is important to include theory from psychology to truly understand the challenges faced by managers, although only a few theories are presented here. More comprehensive reviews are needed in the future. Practical implications: Managers require guidelines based on psychological theory to assist them in overcoming their inabilities in this context. Originality/value: SCM research advocates responsibility for all those affected by this phenomenon, but the lack of theoretical grounding to meet the prevailing psychological challenges hampers the efficacy of putting the current recommendations into business practice. The paper is one of only a few to address managers' psychological challenges in dealing with corporate responsibility across organizational borders and judicial boundaries in supply chains.